Apostolado cívico e trabalhadores do ensino : história do magistério do ensino secundário no Brasil (1931-1946) - Bezerra, Amália Cristina Dias da Rocha (2008)
The research which led to this dissertation had the process of the secondary learning professionalization magistery as a goal, in the period from 1931 to 1946, explaining the point of view from the teacher's graduation for this learning level, as the goals directed to its detinition as a worker. We checked the initiatives of the professionalization magistery due to the federal including initiatives which wanted to organize the school education countrywide in the agreement with the politic, social and economical project of the state. The historiography speaks about the meaning which the education assumed in that historic setting, as a tool of the state in behalf of the nation' s idea construction. The state's initiatives to organize the place of work and the professional magistery statute of secondary learning dates back to the reform of Franscico Campos in 1931,and develops in several ways of normatizations which go through all this period. The education and hea1th's ministries, and the work, industry and trade ministries worked in the professional statute, with selection and the reform of those conditions, in the hiring and in the didatic and pedagogical activities. Because of the secondary learning reform implications about the school work, in social and political functions related to secondary learning, and for all the conceptions about the magistery, we tried to know the social statute of the teaching profession. ln the process of growing secondary learning of the magistery to teach youth under state directions after 1930, under the point of view Civic Apostolate we can show the investigations by which the state could lead a group of knowledgement and behavior that should have guided the teacher in their job about magistery. However, the initiatives of trying to conform the teacher's background with the good effects on their job performace, it was necesssary to consider all the state interference in the magistery conditions of working. Under the point teaching workers we got an analysis of the economical and professional statute of secondary learning teachers' in the process of working organizations. We spoke about regularization of the professional registry and the contracts with private school owners. About Pedro II school, whose the owner is the state, we checked aspects in the teacher' s selections of that institution. The model analysis of the teaching profession of Antonio Nóvoa and the state teory of Antonio Gramsci were confronted with a research of school documents, private files, in way of bringing up biography to this analysed theme.